Proposing a mathematical model of balancing the inventory of multi-zone bicycle sharing systems with mobile stations and applying maintenance constraints - Kaveh, Farshad; Shirouyehzad, Hadi; Hashemkhani Zolfani, Sarfaraz; Arabzad, S. Mohammad (Transport, 2022)
Regarding the necessity of developing transportation infrastructures and its increasing importance in urban issues, nowadays in different cities, bicycles are considered the main and sustainable vehicle along with walking and drawing more attention day by day. The case considers highly paramount since preservation of the environment, natural resources, and energy is one of the significant pillars of sustainable development, and urban transportation intensively influences it. Thus, Bicycle Sharing System (BSS) is recognized as an innovative urban transportation option that meets the citizens’ demand for commuting during the day. The BSS can highly affect the level of citizens’ health, and it can be counted as one of the leading health programs whether it’s added to the public transportation system, it can help the culture to be created to use bicycles instead of cars in most of the internal trips, and also it can be so influential in decreasing the air pollution and in the following its harmful effects on health issues. The mathematical model of rebalancing multi-zone BSS with mobile stations and applying maintenance constraints in a static status is considered in this research. The objective function of this research is a single-objective one, which is modeled with the aims of reducing the costs of traveled distances by the tracks within and outside the zones, reducing the costs of intact and defective bicycles transportation within and outside the zones, and eventually, reducing the costs of surplus bicycles depot at the stations. This issue is a multi-product one that includes different types of bicycles and balancing tracks. Computational results confirm the model’s efficiency. Also, sensitivity analysis has been done to prove that the model is affected by both parameters of storage costs of surplus bicycles and transportation costs within and outside the zones.